Gegenwartsgeschichte der deutschen Wirtschaft : 1945-2020 - Hardach, Gerd † (De Gruyter, 2022)
The topic of this book is the interplay between the economic order and economic development in Germany's various economic systems since 1945 the social market economy of the old Federal Republic of Germany the state socialist planned economy of the German Democratic Republic and the social market economy in unified Germany